A Humanistic Approach to Cultivating Empathy in Inclusive Elementary Schools: An Analysis of Teacher Strategies - Maharani, Tiyara; Faiz, Aiman; Afendi, Arief Hidayat (Journal of Innovation and Research in Primary Education, 2025)
Inclusive schools are a concrete example of equitable education, where all students, including children with special needs, have the same right to a quality education. In this context, teachers play a central role in shaping students' character through a humanistic approach, one of which is instilling the value of empathy. This study aims to describe teachers' humanist strategies in instilling empathy values in inclusive schools. The study was conducted at SDN 2 Kenanga, Cirebon Regency, using a descriptive qualitative approach. Data collection techniques included interviews, observation, and documentation. The results showed that teachers designed learning by integrating the value of empathy into the curriculum, using active methods such as discussion, role-playing, and project-based learning, while also providing role models and habituating values in everyday life. Character evaluation was carried out using a rubric and joint reflection involving both teachers and students. The humanistic approach implemented by teachers successfully created an inclusive atmosphere and supported students’ holistic character development, as reflected in students’ increasing ability to help peers, show concern, and respect differences. This research, however, was limited to one inclusive elementary school that is still in the transition stage, so the findings may not be generalized to all contexts. Nevertheless, the study provides valuable insights into how humanist strategies can effectively strengthen empathy in inclusive educational settings. Teachers are not only instructors but also moral guides who shape students' attitudes and social sensitivity.